2005
DOI: 10.1111/j.0906-6705.2005.00279.x
|View full text |Cite
|
Sign up to set email alerts
|

UVB‐induced leucocyte trafficking in the epidermis of photosensitive lupus erythematosus patients: Normal depletion of Langerhans cells

Abstract: Immunohistopathology of irradiated uninvolved skin of photosensitive LE patients did not reveal the same pathologic trafficking of LCs and neutrophils as described for PLE patients. We conclude that different mechanisms are operative in the pathogenesis of PLE and photosensitive LE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 20 publications
(25 reference statements)
1
16
1
Order By: Relevance
“…Previous investigations have shown an abnormal neutrophil and CD11a/CD68 cell infiltration into the skin of patients with PLE after UVB irradiation (30,32,46). Janssens et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous investigations have shown an abnormal neutrophil and CD11a/CD68 cell infiltration into the skin of patients with PLE after UVB irradiation (30,32,46). Janssens et al.…”
Section: Discussionmentioning
confidence: 99%
“…To that end, Janssens et al. (31) showed that medical photohardening might work by normalizing the UV‐induced cell migratory response in patients with PLE, whereas in systemic lupus erythematosus, UV exposure generally leads to exacerbation of disease (32,33). In patients with PLE, UV‐induced LC depletion and neutrophil influx is impaired, whereas following phototherapy normal cell migratory responses were re‐established and were not statistically different from normal controls (31).…”
Section: Introductionmentioning
confidence: 99%
“…A gradual decrease in epidermal LCs during UV irradiation and reduced numbers of these cells were found in lesional epidermis of CLE patients [64]. A gradual decrease in epidermal LCs during UV irradiation and reduced numbers of these cells were found in lesional epidermis of CLE patients [64].…”
Section: Dendritic Cellsmentioning
confidence: 94%
“…The above-mentioned immunogenetic background as described for SCLE may result in tortuous immunological reactions that result in the production of specific autoantibodies. However, dendritic cells [81][82][83], as well as T lymphocytes and natural killer (NK) cells appear to be involved at different stages and result in the different skin manifestations of LE [84][85][86][87]. In the further disease process, dermal tissue, including extracellular matrix substances, and subsequent inflammatory dermal and epidermal processes result in the clinical pictures presented above [88][89][90][91][92][93].…”
Section: Prognosis Of Cutaneous Lupus Erythematosusmentioning
confidence: 99%